2016
DOI: 10.1212/wnl.0000000000002767
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome following maternal exposure to pregabalin may call for concern

Abstract: This study demonstrated a signal for increased risk of major birth defects after first trimester exposure to pregabalin. However, several limitations such as the small sample size, differences across groups in maternal conditions, and concomitant medication exposure exclude definitive conclusions, so these results call for confirmation through independent studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 20 publications
0
56
0
2
Order By: Relevance
“…Many of the same authors of the gabapentin study reported on pregnancy outcomes following in utero pregabalin exposure [18]. In this multicenter, prospective observational study across 8 participating Teratology Information Services in 7 countries, the prescribing indication for pregabalin was epilepsy in only 3.0 % of the women; the most common indications were pain (neuropathic pain and migraine; 74.3 %) and psychiatric disorders (45.1 %), with obvious overlaps.…”
Section: Pregabalinmentioning
confidence: 97%
“…Many of the same authors of the gabapentin study reported on pregnancy outcomes following in utero pregabalin exposure [18]. In this multicenter, prospective observational study across 8 participating Teratology Information Services in 7 countries, the prescribing indication for pregabalin was epilepsy in only 3.0 % of the women; the most common indications were pain (neuropathic pain and migraine; 74.3 %) and psychiatric disorders (45.1 %), with obvious overlaps.…”
Section: Pregabalinmentioning
confidence: 97%
“…1 Of 116 infants exposed during the first trimester, 7 (6%) had structural malformations compared to 12 of 580 (2.1%) in the reference group. The imbalance was largely explained by 4 cases of cerebral ventricle enlargement (3.2%) in the exposed group compared to 3 (0.5%) in the control group.…”
mentioning
confidence: 92%
“…The structure and composition of these data are very similar to those of MAX, and the methods we used to create the linked cohort and to analyze the data followed the same protocol. Finally, we added the adjusted estimates from the MAX and the MarketScan populations to the crude estimates of the recent multicenter study 1 and estimated a pooled RR using the DerSimonian and Laird random-effects model. We considered the crude estimates provided by the multicenter study to be adjusted because the authors reported that adjustment did not change the point estimates.…”
mentioning
confidence: 99%
“…Discussions should include careful risk-benefi t assessment of reasonable treatment options for the patient's seizure or epilepsy type; 3) for seizure (or epilepsy) types where valproate is the most eff ective treatment, the risks and benefi ts of valproate and other treatment alternatives should be discussed; 4) valproate should not be prescribed as a fi rst-line treatment for focal epilepsy; 5) valproate may be offered as a fi rst-line treatment for epilepsy syndromes where it is the most eff ective treatment, including idiopathic (genetic) generalized syndromes associated with tonic-clonic seizures; 6) valproate may be off ered as a fi rst-line treatment in situations where pregnancy is highly unlikely (e.g., signifi cant intellectual or physical disability); and 7) women and girls taking valproate require regular follow-up for ongoing consideration of the most appropriate treatment regimen 41 . For newer AEDs, one multicenter, observational prospective cohort study conducted by our ENTIS colleagues in 2016 demonstrated a signal for an increased risk of major birth defects after fi rst trimester exposure to pregabalin, but these results need confi rmation through independent studies 42 . Newer data also suggest that lamotrigine and levetiracetam are associated with a relatively low risk for both anatomic and developmental adverse eff ects, although further studies are needed for these and other AEDs 43 .…”
Section: Congenital Malformations Pervasive and Behavioral Aspects mentioning
confidence: 99%